(untitled) (Research, Society and Development, 2019)
I This study is an excerpt from the master’s research on digital literacy: technological insertions in the educational context of the pedagogue, which is underway at the Master in Humanities and Languages Teaching at the Franciscan University of Santa Maria, RS. We are in a digital age, where subjects are required to practice digital literacy, which involves social practices of reading and writing in digital media. To this end, we chose the following specific objective: to explore digital literacy and its insertion in the pedagogical academic formation. In order to study the concept of digital literacy in its theoretical conception, we opted for a literature review about the concept. Thus, it was observed that digital literacy, in addition to addressing social reading and writing practices on digital devices, also involves the formation of a critical and reflective subject, who uses these social reading and writing practices.